Correlation between Platelets and Red Blood Cells Parameters in Cattle Theileriosis - Abd Ellah, Mahmoud Rushdi (Journal of Hematology Research, 2015)
The purpose of the study is to investigate the values for platelets (PLT) count, plateletcrit (PCT), mean platelet volume (MPV), platelet distribution width (PDW) and the correlation with the parallel red blood cell parameters, packed cell volume (PCV), mean corpuscular volume (MCV), and red blood cell distribution width (RDW) in cattle Theileriosis. A total number of 25 cows were subjected to study. Out of them 18 cows were suffered from Theileriosis, the remained 7 cows were clinically healthy and kept as control. Red blood cells (RBCs) and platelet indices were measured in whole blood samples collected on EDTA. Animals infected with Theileria were classified into two groups based on total erythrocytes count. Group 1: included animals that had total RBCs count above 5 x 106/mm3. Group 2: included animals that had total RBCs count below 5 x 106/mm3. Comparing data from theileria infected groups with the control group revealed that there was a significant decrease in total RBCs count only in group 2 (p<0.01). MCV showed significant decreases in group 1 (p<0.01) and group 2 (p<0.05), PCV was significantly decreased in both groups (p<0.01), RDW was significantly increased only in group 2 (p<0.05), PLT count was significantly decreased only in group 2 (p<0.05), PCT was significantly decreased only in group 2 (p<0.05), no significant changes were observed in MPV and PDW. Comparing data from group 1 with group 2 revealed that RBCs count, PCV and PLT count were significantly higher in group 1 than group 2. Furthermore, MCV value was significantly higher in group 2 than group 1. RDW was significantly higher in group 2 than group 1. The present study revealed that in cattle Theileriosis, PLT indices greatly affected by the degree of anemia. Furthermore, the decrease in PLT count and PCT usually accompany oligocythemia.